Splitting CO2 with a ceria‐based redox cycle in a solar‐driven thermogravimetric analyzer. Issue 4 (5th October 2016) - Takacs, M.; Ackermann, S.; Bonk, A.; Neises‐von Puttkamer, M.; Haueter, Ph.; Scheffe, J. R.; Vogt, U. F.; Steinfeld, A.
Abstract : Thermochemical splitting of CO2 via a ceria‐based redox cycle was performed in a solar‐driven thermogravimetric analyzer. Overall reaction rates, including heat and mass transport, were determined under concentrated irradiation mimicking realistic operation of solar reactors. Reticulated porous ceramic (RPC) structures and fibers made of undoped and Zr 4+ ‐doped CeO2, were endothermally reduced under radiative fluxes of 1280 suns in the temperature range 1200–1950 K and subsequently re‐oxidized with CO2 at 950–1400 K. Rapid and uniform heating was observed for 8 ppi ceria RPC with mm‐sized porosity due to its low optical thickness and volumetric radiative absorption, while ceria fibers with μm‐sized porosity performed poorly due to its opacity to incident irradiation. The 10 ppi RPC exhibited higher fuel yield because of its higher sample density. Zr 4+ ‐doped ceria showed increasing reduction extents with dopant concentration but decreasing specific CO yield due to unfavorable oxidation thermodynamics and slower kinetics. © 2016 American Institute of Chemical Engineers AIChE J, 63: 1263–1271, 2017